Alterations in the human microbiome and its implications on cancer risk: microbiome and carcinogenesis - Parida, Sheetal (Henry Stewart Talks, 2023)
The breast microbiome, Cancer microbiome, Microbiome and carcinogenesis, Enterotoxigenic B. fragilis, F. nucelatum, Gut microbiota and cancer progression